Echinococcosis 2017
DOI: 10.5772/intechopen.69031
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Complications of Hepatic Hydatid Cyst Surgery and Prevention Methods

Abstract: Cystic echinococcosis is still one of the main reasons for liver surgery especially in endemic areas. The most common complication of liver hydatid cyst is cystobiliary communication (CBC). Preoperative or intraoperative diagnosis of CBC is essential for the treatment, since it leads to postoperative bile leakage and fistula formation eventually without intervention. Predictive factors such as cyst size, history of jaundice, and degenerated cysts are described for preoperative evaluation. Further preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Literature in the 90s reported that the treatment of hydatid cyst was surgical, and if the cyst was associated with the biliary tract during surgery, T-tube drainage might be required, and preoperative preparation should be made (126). However, today, with the advancement of radiological imaging, cysto-biliary communication can be better demonstrated preoperatively, and sphincterotomy and preoperative ERCP reduce the risk of postoperative bile leakage (124,126).…”
Section: Management Of Hydatid Cyst With Cysto-biliary Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature in the 90s reported that the treatment of hydatid cyst was surgical, and if the cyst was associated with the biliary tract during surgery, T-tube drainage might be required, and preoperative preparation should be made (126). However, today, with the advancement of radiological imaging, cysto-biliary communication can be better demonstrated preoperatively, and sphincterotomy and preoperative ERCP reduce the risk of postoperative bile leakage (124,126).…”
Section: Management Of Hydatid Cyst With Cysto-biliary Communicationmentioning
confidence: 99%
“…Literature in the 90s reported that the treatment of hydatid cyst was surgical, and if the cyst was associated with the biliary tract during surgery, T-tube drainage might be required, and preoperative preparation should be made (126). However, today, with the advancement of radiological imaging, cysto-biliary communication can be better demonstrated preoperatively, and sphincterotomy and preoperative ERCP reduce the risk of postoperative bile leakage (124,126). There are also recommendations in the literature for the use of ERCP to reduce bile duct pressure and clear debris in hydatid cysts with an obvious cysto-biliary communication, since the incidence of detecting bile duct association greater than 5 mm is 65%, while the incidence of detecting biliary fistula below 5 mm is between 10-37% (112,126,127).…”
Section: Management Of Hydatid Cyst With Cysto-biliary Communicationmentioning
confidence: 99%
See 1 more Smart Citation